Global Governance in the Context of BRI and CPEC: Heritage Challenges and Opportunities in Pakistan - Chawla, Muhammad Iqbal (Annals of Human and Social Sciences, 2025)
This study underscores the importance of Pakistan’s religio-cultural heritage, highlighting its historical legacy of pluralism, tolerance, and coexistence. It asserts that Pakistan’s rich tangible heritage deserves greater global recognition. Pakistan’s diverse religious traditions—spanning Islam, Hinduism, Sikhism, Buddhism, and Christianity—present a significant opportunity for faith-based tourism. With 120 out of 480 tourist destinations being religious sites, the country’s growing appeal is evident in its rise on the International Travel and Tourism Development Index, climbing from 89th in 2019 to 83rd in 2021. Collaborative Opportunities: By examining key religious sites and past partnerships, this study explores ways to strengthen cultural ties and advance global heritage tourism. China’s Global Civilization Initiative promotes cross-cultural dialogue, fostering international harmony. This research adopts a social history approach, employing historical methodology that relies on primary and secondary sources to reconstruct and analyze the socio-cultural past. Pakistan, with its untapped potential in religious tourism, stands to benefit significantly from Chinese tourist interest. As China invests in human capital and cultural exchange, this research investigates how the Belt and Road Initiative (BRI) and the China-Pakistan Economic Corridor (CPEC) can boost religio-cultural tourism in Pakistan. By identifying challenges and opportunities, the study emphasizes how tourism development can spur economic growth while enhancing Pakistan’s global image. This research adopts a social history approach, employing historical methodology that relies on primary and secondary sources to reconstruct and analyze the socio-cultural past. While substantial scholarly attention has been devoted to analyzing CPEC's economic, infrastructural, and political dimensions, its sociocultural implications - particularly in the realm of religious tourism - have received comparatively limited examination. This study seeks to address this scholarly gap by offering a critical intervention in the existing historiography.